Unplugged Activities in Cross-Curricular Teaching: Effect on Sixth Graders’ Computational Thinking and Learning Outcomes - José Miguel Merino-Armero; José Antonio González-Calero; Ramón Cózar-Gutiérrez; Javier del Olmo-Muñoz (Multimodal Technologies and Interaction, 2022)
There is a debate about the way to introduce computational thinking (CT) in schools. Different proposals are on the table; these include the creation of new computational areas for developing CT, the introduction of CT in STEM areas, and the cross-curricular integration of CT in schools. There is also concern that no student should be left behind, independently of their economic situation. To this effect, an unplugged approach is the most cost-effective solution. In addition, this topic is interesting in the context of a pandemic situation that has prevented the sharing of materials between students. This study analyzes an unplugged cross-curricular introduction of CT in the Social Sciences area among sixth grade students. A group of 14 students was selected to carry out an unplugged intervention design—where they were required to program an imaginary robot on paper—in the Social Sciences area. Their CT development and academic results were compared to those of 31 students from the control group who continued attending regular classes. Results showed that an unplugged teaching style of CT in Social Sciences lessons significantly increased CT (p < 0.001) and with a large effect size (d = 1.305) without differences in students’ academic achievement. The findings show that children can potentially develop their CT in non-STEM lessons, learning the same curricular contents, and maintaining their academic results.